2009
DOI: 10.1021/ma900332d
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Poly(divinylbenzene) Microspheres via Thiol−Ene Chemistry and Alkyne−Azide Click Reactions

Abstract: We report the functionalization of cross-linked poly(divinylbenzene) (pDVB) microspheres using both thiol-ene chemistry and azide-alkyne click reactions. The RAFT technique was carried out to synthesize SH-functionalized poly(N-isopropylacrylamide) (pNIPAAm) and utilized to generate pNIPAAm surface-modified microspheres via thiol-ene modification. The accessible double bonds on the surface of the microspheres allow the direct coupling with thiol-end functionalized pNIPAAm. In a second approach, pDVB microspher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 37 publications
2
151
0
1
Order By: Relevance
“…tBA [283] 162 [339] S S C 4 H 9 S -C 163 [339] S S Ph N N N C 4 H 9 S BA [339] St [339] 164 [348] S S C 3 H 7 S MA [349] 165 [350] St [350] St-b-MA [350] 166 [351] S S C 4 H 9 S (BA) [351] (St) [351] (St-b-BA) [351] (BA-b-St) [351] 167 [337] S S C 6 H 13 S St [337] 168* [352] S S C 12 H 25 S 319 [352] (Continued) [283] St [283,353] 170 [283] S S S HO 2 C AA [354] DMAM [218] NIPAM [355] St [218,283] (St) [356] (SSO3Na) [167] DADMAC [357] 346 [358] AA-b-SSO3Na [354] 346-b-DMAM [358] (St-b-DMAM) [218] 171 [349] MA [349] MA-b-St [349] 172 [226] S S Br Ϫ N C 12 H 25 S ϩ St [226] 173 [227] 176 [350,360] POSS macro-RAFT agent…”
Section: S S Cn C 2 H 5 Smentioning
confidence: 99%
See 1 more Smart Citation
“…tBA [283] 162 [339] S S C 4 H 9 S -C 163 [339] S S Ph N N N C 4 H 9 S BA [339] St [339] 164 [348] S S C 3 H 7 S MA [349] 165 [350] St [350] St-b-MA [350] 166 [351] S S C 4 H 9 S (BA) [351] (St) [351] (St-b-BA) [351] (BA-b-St) [351] 167 [337] S S C 6 H 13 S St [337] 168* [352] S S C 12 H 25 S 319 [352] (Continued) [283] St [283,353] 170 [283] S S S HO 2 C AA [354] DMAM [218] NIPAM [355] St [218,283] (St) [356] (SSO3Na) [167] DADMAC [357] 346 [358] AA-b-SSO3Na [354] 346-b-DMAM [358] (St-b-DMAM) [218] 171 [349] MA [349] MA-b-St [349] 172 [226] S S Br Ϫ N C 12 H 25 S ϩ St [226] 173 [227] 176 [350,360] POSS macro-RAFT agent…”
Section: S S Cn C 2 H 5 Smentioning
confidence: 99%
“…[117,130,479] This methodology has been applied to the synthesis of three-armed stars by an in-situ thiol-ene reaction with a triacrylate [130] and has been applied to directly make biopolymer conjugates. [479] A recent study shows that dithioester and trithiocarbonate RAFT agents [R-SC(S)Z] undergo a radical-catalyzed reaction with thiols that results in oxidation of the thiol to a disulfide and concomitant reduction of the RAFT agent to R-H. [481] The relative rates of reaction suggested that dithioester RAFT agents [204] PEGA Ph (58) Butylamine Used in thiol-ene [204] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP/HEA butylamine/TCEP/BA One-pot thiol-ene [373] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP Used in thiol-ene [371,372] NIPAM Ph (25) LiB(C 2 H 5 ) 3 H Used in thiol-ene [151] NIPAM S(CH 2 ) 2 CO 2 H (170) NaBH 4 Used in thiol-ene [355] NIPAM SC 4 H 9 (166) NaOH/MeOH/EDTA Used in thiol-ene [412] NIPAM Ph (24) Octylamine/DMPP/AMA One-pot thiol-ene [132] NIPAM Ph (24) Octylamine/DMPP/PMA One-pot thiol-ene [132] DEAM Ph (24) Hexylamine/DMPP/MA One-pot thiol-ene [130] St Ph (24) Propylamine/PBu 3 /MA NaBH 4 /PBu 3 /MA One-pot thiol-ene [117] St Ph (24) Propylamine NaBH 4 [205] MMA Ph (82) Hexylamine Conditions to favour disulfide formation [196] MMA Ph (22) Propylamine One-pot methanethiosulfonate [480] NVP OC 2 H 5 (228) NaBH 4 Used in peptide/nucleotide conjugation [396] A Monomer unit adjacent to thiocarbonylthio group. B TCEP -tris(2-carboxyethyl) phosphine hydrochloride, EDTA -ethylenediaminetetraacetic acid, TCEP -tris(2-carboxyethyl phosphine), DMPPdimethylphenylphosphine.…”
Section: Aminolysis/hydrolysis/ionic Reductionmentioning
confidence: 99%
“…Methacrylate crosslinkers are also polymerized via precipitation polymerization with a low percentage of added monomer [50][51]. As a result, precipitation polymerized particles are rich in remaining double bonds that can be efficiently utilized in post-functionalization [52] (see further functionalization section). As the polymerization starts, oligomers and nuclei are being formed (Fig.…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…A combination of thiol-ene and CuAAC click reactions on nonporous polyDVB particles was published by Müller et al [52]. Remaining double bonds of precipitation polymerized polyDVB particles first underwent thiol-ene click by treatment with 1-azidoundecan-11-thiol.…”
Section: Thio-click Modificationsmentioning
confidence: 99%
“…The second step for the synthesis of POSS-S-PA from POSS-SH is explained as follows: The methacrylic PA-terminated hybrid-network polymer POSS-S-PA was synthesized by the so-called "thiol-ene" reaction [19,23,24] using POSS-SH and EGMP. For synthesis, 10 mL of POSS-SH (10.1800 g, 1000 mL, and 10 mM) dissolved in 30 mL of anhydrous DCM and TEA (0.24 mM) were taken in a three-necked round bottom flask and subjected to constant stirring under an N 2 atmosphere for about 2 h at 40 • C. Then, freshly distilled EGMP (16.8080 g, 1000 mL, and 80 mM) was injected into the reaction mixture to carry out the polymerization reaction for 5 h at 40 • C. In order to retain the POSS-cage structure, EGMP was added slowly, dropwise, for up to 30 minutes.…”
Section: Synthesis Of Poss-s-pamentioning
confidence: 99%